2018
DOI: 10.1177/1069072718813368
|View full text |Cite
|
Sign up to set email alerts
|

Work Value Differentiation and Profile Elevation: What Do They Predict?

Abstract: The current study examined work value differentiation and profile elevation (PE). Using a sample of 251 college students who provided data on the O*NET Work Importance Profiler online, it was found that (1) when differentiation of work values was calculated using three indices (i.e., high–low differentiation, Iachan differentiation, and variance differentiation), only Iachan differentiation positively related to indecision; (2) none of the three indices of differentiation related to career maturity; (3) work v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…The third validation stage is evidence based on relation to other variable. Some previous study found that work value orientation plays an important role in various career consequences such as career planning, career decision-making, career self-efficacy, career sustainability, career maturity, and career certainty (Chi et al, 2019 ; Doo and Park, 2019 ; Kelly et al, 2020 ). Based on the result of this study, we found that work value significantly correlated with career development learning (CDL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third validation stage is evidence based on relation to other variable. Some previous study found that work value orientation plays an important role in various career consequences such as career planning, career decision-making, career self-efficacy, career sustainability, career maturity, and career certainty (Chi et al, 2019 ; Doo and Park, 2019 ; Kelly et al, 2020 ). Based on the result of this study, we found that work value significantly correlated with career development learning (CDL).…”
Section: Discussionmentioning
confidence: 99%
“…As of, the instrument can be used for the latest generation (Generation Z), which is the final year students in higher education. Thus, far, many of the studies addressing this importance of understanding the work value in final year students and graduates (De Cooman and Dries, 2012 ; Shujaat, 2014 ; Kuron et al, 2015 ; Ros et al, 2015 ; Chi et al, 2019 ; Doo and Park, 2019 ; Hampton and Welsh, 2019 ; Neyt et al, 2019 ). However, the instrument used was not specific for students in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to self-control, various strengths that belong to this factor have been related to career self-doubt. Prudence, measured with conscientiousness subscales [37][38][39][40][41], and self-regulation strengths have shown negative associations with career self-doubt in undergraduates [42]. Concerning inquisitiveness, several strengths that form this factor have been associated with career self-doubt.…”
Section: Character Strengths As Predictive Factors Of Academic Engagement Career Self-doubt and Academic Performancementioning
confidence: 99%
“…Informasi ini menjadi sangat membahayakan bagi seluruh mahasiswa yang akan tamat kuliah dari universitas. Menurut Chi, Leuty, Bullock Yowell & Dahlen (2018) didapati rendahnya kematangan karir mahasiswa yang memberi dampak negatif terhadap emosional dan prestasi mahasiswa. Sikap mahasiswa menjadi tidak memliki keranian dan rendah kepercayaan dirinya untuk menggapai sesuatu yang diinginkannya.…”
Section: Empati Remaja Terhadap Korban Bullying DI Pekanbaruunclassified